Velvet Antler Peptides Reduce Scarring via Inhibiting the TGF-β Signaling Pathway During Wound Healing - Zhang, Guokun; Wang, Dongxu; Ren, Jing; Sun, Hongmei; Li, Jiping; Wang, Shengnan; Shi, Liyan; Wang, Zhen; Yao, Mengjie; Zhao, Haiping; Li, Chunyi (Frontiers in Medicine, 2022)
Aim Scar formation generally occurs in cutaneous wound healing in mammals, mainly caused by myofibroblast aggregations, and currently with few effective treatment options. However, the pedicle wound (about 10 cm in diameter) of the deer can initiate regenerative healing, which has been found to be achieved via paracrine factors from the internal tissues of antlers. Methods Enzymatically digested velvet antler peptides (EVAP) were prepared along with other types of antler extracts as the controls. The effects of EVAP on healing of full-thickness skin wounds were evaluated using rats in vivo, and on myofibroblast transdifferentiation tested using transforming growth factor-β1 (TGF-β1)-induced human dermal fibroblasts in vitro. Results EVAP significantly accelerated the wound healing rate, reduced scar formation, and improved the healing quality, including promoted angiogenesis, increased number of skin appendages (hair follicles and sebaceous glands) and improved the distribution pattern of collagen fibers (basket-wave like) in the healed tissue. Moreover, EVAP significantly down-regulated the expression levels of genes pro- scar formation (Col1a2 and TGF-β1), and up-regulated the expression levels of genes anti-scar formation (Col3a1 and TGF-β3), and suppressed the excessive transdifferentiation of myofibroblasts and the formation of collagen I in vivo and in vitro. Furthermore, we found these effects were highly likely achieved by inhibiting the TGF-β signaling pathway, evidenced by decreased expression levels of the related genes, including TGF-β1, Smad2, p-Smad2, α-SMA, and collagen I. Conclusions EVAP may be a promising candidate to be developed as a clinic drug for regenerative wound healing.